Molecular systems for the characterization of fungi of the genus Aspergillus - Stefano Andreoni (Microbiologia Medica, 2011)
Taxonomy is generally considered a synonym of systematics and is traditionally divided into classification, nomenclature and identification, the process of determining whether an unknown organism belongs to one of the units defined. The new taxonomies are based on a polyphasic approach using phenotypical characters together with multigene DNA sequences. The term “polyphasic” taxonomy described the integration of all available genotypic, phenotypic, and phylogenetic information into a consensus type of classification. These information can be used to classify fungi belong to the genus Aspergillus. Over the years, many different molecular methods have been developed for Aspergillus strain typing and to investigate the epidemiological relation between environmental and clinical isolates. Several typing methods have been described for Aspergillus species: restriction fragment lenght polymorphisms (RFLP), Random Amplification Polymorphic DNA (RAPD), Amplified Fragment Length Polymorphism (AFLP), Multilocus sequenze typing (MLST) and Random amplified microsatellites (RAMS). The advantages and disavantages of the different typing techniques are evaluated in terms of their discriminatory power, reproducibility and exchangeability, applicability, easy of use, and interpretation.